The effect of digital ethics as a civic virtue on ChatGPT misuse behavior among high school students - Sapulette, Marlyen Sharly (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
The development of artificial intelligence technology, such as ChatGPT, has had a significant impact on education worldwide, including in Ambon City. However, its use often raises the risk of misuse, especially in cases of plagiarism, task manipulation, or the instant completion of academic assignments. The research method used is a descriptive, non-experimental, quantitative approach, with 120 high school students in Ambon City as respondents. This research aims to analyse the association between digital ethics as a civic virtue and ChatGPT misuse, and to identify the relationship between indicators in both variables. The research instrument consisted of 15 indicators of digital ethics and 15 indicators of ChatGPT misuse. The results showed that the digital ethics instrument had very good reliability (Cronbach's Alpha = 0.867), and ChatGPT misuse behaviour also had very high reliability (Cronbach's Alpha = 0.932). Fourteen of the 15 indicators of digital ethics and all indicators of ChatGPT misuse were declared valid. This research also showed a positive and significant influence between digital ethics and ChatGPT misuse behaviour (r = 0.203, p = 0.027). Although the correlation is weak, a p-value <0.05 indicates that the relationship remains significant. This relationship suggests that students who have knowledge of digital ethics do not always practice ethical behaviour when using ChatGPT. This finding provides new insights into the complexity of students' digital behaviour, suggesting that an understanding of digital ethics does not always guarantee ethical behaviour in the digital realm, necessitating the need for more effective digital citizenship education strategies.